Risk Compounds, Preclinical Toxicity Evaluation, and Potential Mechanisms of Chinese Materia Medica–Induced Cardiotoxicity - Zhou, Jie; Peng, Fu; Cao, Xiaoyu; Xie, Xiaofang; Chen, Dayi; Yang, Lian; Rao, Chaolong; Peng, Cheng; Pan, Xiaoqi (Frontiers in Pharmacology, 2021)
Chinese materia medica (CMM) has been applied for prevention and treatment of diseases for thousands of years. However, arrhythmia, myocardial ischemia, heart failure, and other cardiac adverse reactions during the clinical application of CMM were gradually reported. CMM-induced cardiotoxicity (CMMIC) has aroused widespread international attention. Safety evaluation system of CMM needs to be established urgently to restore the image and status of CMM. Our review aims to summarize the risk components, preclinical toxicity evaluation, and potential mechanisms of CMMIC. All relevant articles published on the PubMed, Embase, and China National Knowledge Infrastructure (CNKI) databases for the latest twenty years were searched and manually extracted. The risk ingredients of CMMIC are relatively complex. A single CMM usually contains various risk components, while the same risk substance may exist in various CMM. The active ingredients and risk components in CMM can be transformed into each other under different conditions, such as drug dosage, medication methods, and body status. Generally, the risk components of CMMIC include alkaloids, terpenoids, steroids, heavy metals, organic acids, toxic proteins and peptides. Traditional evaluation methods of chemical drugs-induced cardiotoxicity primarily include cardiac function monitoring, endomyocardial biopsy (EMB), myocardial zymogram (MZ) and biomarkers determination, while evaluation of CMMIC lacks specific indicators. In preclinical stage, CMMIC should be systematically evaluated at integral, tissular, cellular and molecular levels, including cardiac function, histopathology, cytology, MZ, and traditional biomarkers. Thanks to the development of systematic biology, the higher specificity and sensitivity of biomarkers, such as genes, proteins, and metabolic small molecules are gradually applied for evaluating CMMIC. Previous studies on mechanisms of CMMIC are focused on a single drug, monomer or components of CMM. The interaction between ion homeostasis (sodium, potassium, and calcium ions), oxidative stress, mitochondrial damage, apoptosis and autophagy, and metabolic disturbance is involved in CMMIC. Clarification on the risk components, preclinical toxicity evaluation, and potential mechanisms of CMMIC must be beneficial to guide new CMM development and post-marketed CMM reevaluation.